Os jovens da favela. Reflexões sobre controle e contenção sócio-espacial dos párias urbanos no Rio de Janeiro - Fernando Lannes-Fernandes (Universidad Autónoma del Estado de México, 2012)
This article outlines a reflection on analytic tools which can contribute in studies about urban segregation and socio-spatial stigmatisation. The urban space production in Rio de Janeiro and the social representation of Favelas is utilized as an empiric reference for a theoretical discussion, in which two analytical notions are introduced: the ¿socio-spatial control and enclosure¿ and the ¿space of embarrassment¿.